PENGARUH SUMBER DAYA MANUSIA, PENATAUSAHAAN, PENGAWASAN BARANG MILIK DAERAH TERHADAP PENGAMANAN BARANG MILIK DAERAH (Studi Pada SKPD Pemerintah Kabupaten Buol) - Bokingo, Aljufri (Katalogis, 2017)
The study aims to determine and analyze simultaneous and partial influences of human resource, administration, and monitoring on securing local-owned properties in govermental working units in Buol Regency. Population consists of 52 units in Buol, sample determined with census sampling. Respondents of 104 people consist of heads of financial and assets divisions and properties caretakers. Data collected through questionnaires and analyzed with statistical package for social science program. Method of analysis is multiple linear regressions. The study finds that: 1) human resource, administration, and monitoring simultaneously have significant influence on securing local-owned properties in governmental working units in Buol Regency; 2) human resource partially has insignificant influence on securing local-owned properties in governmental working units in Buol Regency; 3) administration partially has significant influence on securing local-owned properties in governmental working units in Buol Regency; 4) monitoring partially has significant influence on securing local-owned properties in governmental working units in Buol Regency.